An Introduction to Book Staying Ok - Akbar Zare Shahabadi; Hamideh Shiri-Mohammadabad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Over the last two decades, a change has occurred in the paradigm of the development model, especially individual and social development, and the theoretical model of dynamic human training has been attracting considerable interest since then. Indeed, humans and their needs were viewed from a different angle, and the communities set it as their goal to educate and train psychologically and socially good/OK humans. Thomas A. Harris, an American author, is one of the noted psychiatrists who has researched this subject for several decades. He has written several books on the good status and the good human. He believes that good training bred good status. This article firstly provides a short introduction about the book, and then in the second part, the Transactional Analysis Theory is introduced, and then the structure and content of the book are mentioned in the third part. In the rest of the paper, the criticisms and evaluation of the book are presented in two sub-sections (a) evaluation of form and (b) evaluation of the content. In the final section of the paper, the conclusion of the book is presented.